Financial Development, Remittances, and Real Exchange Rate Appreciation - Acosta, Pablo A.; Baerg, Nicole Rae; Mandelman, Federico S. (2012)
For developing countries, remittances are an important and expanding source of capital, equivalent to two-thirds of overall foreign direct investment and nearly 2 percent of gross domestic product. This article examines the relationship between remittance inflows, financial sector development, and the real exchange rate. The authors test whether financial sector development can prevent appreciation of the real exchange rate. In particular, they show that well-developed financial sectors can more effectively channel remittances into investment opportunities. Using panel data for 109 developing and transition countries for 1990-2003, the authors find that remittances by themselves tend to put upward pressure on the real exchange rate. But this effect is weaker in countries with deeper and more sophisticated financial markets, which seem to retain trade competitiveness.